Disrupting “Asian Religious Studies”: Knowledge (Re)production and the Co-construction of Religion in Singapore - Kong, Lily (Numen, 2015)
In this article, I begin with the position that knowledge production and reproduction is partial and situated. Through an examination of academic research on and teaching of religion in Singapore, I demonstrate how scholarly interventions at once re-present and conceal religion as experienced and lived. I posit that the partiality of such interventions is due to the influential official narrative about religion in Singapore, so that what is studied and taught reflects certain dimensions of religious life and religious-secular relations that dominate official discourse. In particular, through academic writing (and to a lesser extent, teaching), religion in Singapore is constructed as a particular mosaic of social, cultural, and political life, socially relevant, culturally rich, spatially manifested, transnationally linked, politically delicate, and historically steeped. Drawing from this reflection on Singapore, I emphasize the need to recognize the geography, sociology, and politics of knowledge (re)production, and to decenter the notion that there is an emerging “Asian religious studies.”